Habitat use by caribou in northern Alberta, Canada - Schneider, Richard R.; Wynes, B.; Wasel, S.; Dzus, E.; Hiltz, H. (Rangifer, 2000)
Habitat mapping and habitat supply assessment have been identified as key elements of the Alberta Woodland Caribou Conservation Strategy. Previous studies from northeastern Alberta have shown that caribou select lowland habitat types and avoid upland. The objectives of our study were to determine whether these selection patterns are consistent across all of northern Alberta and to generate a map of habitat suitability for the entire region. Our database included over 11 000 radiotelemetry locations collected over six years from caribou across northern Alberta. We also had available a recently revised map of peatlands for the entire province. We found that polygons in the peatland map containing greater than 30% bog were selected by caribou. Fens were also selected, but not as strongly as bogs. Habitat polygons containing greater than 50% non-peat were avoided. These findings were consistent among all regions studied, and among years. The proportion of caribou relocations declined exponentially with distance from polygons classified as peatlands. Based on the observed selection patterns, we reclassified the peatland map to reflect the potential suitability of habitat for caribou across northern Alberta.